Encouraging Difficult Conversations in Mitigating Nursing Faculty Shortages - Smith, Jenette; Perez, Miguel A. (Horizonte Sanitario, 2024)
Despite numerous efforts to address the global nursing shortage, recent figures suggest it is not just a persistent problem, but one that is escalating. The authors delve into the underlying issues related to the nursing shortage and propose urgent solutions that can reverse this alarming trend.